Risiko reputasi akibat kejahatan digital: studi kasus kebocoran data nasabah dan respons publik di media sosial - Irawati, Indriana (Maliki Interdisciplinary Journal, 2025)
The digital transformation in the banking sector has significantly improved public access to financial services, yet it has also increased the risk of cybercrime, including personal data breaches. This study examines the reputational impact caused by the 2023 customer data breach at Bank Syariah Indonesia (BSI), and how social media plays a key role in shaping public perception. The research employs a literature review and public response analysis through digital platforms. Findings indicate that negative reactions on social media can rapidly damage a company’s image and have long-term consequences on public trust. Therefore, banking institutions must develop robust cybersecurity systems, implement effective crisis communication strategies, and manage their digital reputation proactively through social media.